Shared Goals, Different Barriers: A Qualitative Study of UK Veterinarians' and Farmers' Beliefs About Antimicrobial Resistance and Stewardship - Golding, Sarah E.; Ogden, Jane; Higgins, Helen M. (Frontiers in Veterinary Science, 2019)
Although much research has investigated the drivers of inappropriate antimicrobial prescribing in human medicine, equivalent research in veterinary medicine is in its infancy. This qualitative study used a critical incident approach to explore farm veterinarians’ (vets) and farmers’ beliefs about antimicrobial use and antimicrobial stewardship. Semi-structured interviews were conducted with 13 vets and 12 farmers in the UK, who worked mostly with beef cattle, dairy cattle and sheep, but a minority also worked with pigs or poultry. An inductive thematic analysis was conducted to explore how vets and farmers understood their responsibilities towards stewardship and antimicrobial resistance (AMR) and to identify key similarities and differences between the professions. The analysis generated four themes: ‘A shared conflict between ideals and behaviour’, ‘Barriers to stewardship: the vets’ perspective’, ‘Barriers to stewardship: the farmers’ perspective’, and ‘A shared ambivalence: ownership versus other-blaming’. Vets and farmers demonstrated good understanding of stewardship but their treatment decisions are not always aligned to stewardship principles. Various barriers to improving antimicrobial stewardship were discussed by vets and farmers, but they placed differing emphasis on specific barriers. Faced with these barriers and an awareness that antimicrobial usage is not always aligned to stewardship principles, vets and farmers expressed frustration and a sense of ambivalence towards stewardship, and also engaged in other-blaming for the problem of AMR. In conclusion, vets and farmers in this study seem motivated to be antimicrobial stewards but feel challenged by the day-to-day reality of their jobs; they experience ambivalence towards their responsibilities for AMR, which may negatively impact their motivation to always act as antimicrobial stewards. Successfully tackling AMR will require change at the individual-, group-, and societal-level. Future interventions to improve antimicrobial usage in livestock farming could be situated within a social ecological framework, where other-blaming between professions is seen as a result of the interplay between psychological and contextual factors. Other-blaming could be reduced using a social identity approach; a common ingroup identity could be created by encouraging vets and farmers to focus on their common goal, namely a shared desire to promote animal welfare through optimal antimicrobial stewardship.